Heavy Alkyl-Benzene Sulfonate-Controlled Growth of Aragonite-Based Polymorphic CaCO3 Crystals in Emulsion - Weiwei He; Junqing Hu; Weihao Sun; Jiqiong Liu; Hongguang Guo; Changming Zhao; Qingguo Wang; Xiangbin Liu; Meng Cai; Weiguang Shi (Crystals, 2023)
The non-natural mineralization of CaCO3 with special structures or morphologies is generated during the migration of crude oil and is the main form of scale in alkaline/surfactant/polymer (ASP) flooding in oilfields, adversely affecting oil recovery and causing environmental pollution. To date, the mineralization of aragonite superstructures and the role of heavy alkyl-benzene sulfonate (HABS) in mineralization are still unclear. In this work, aragonite-based superstructures of CaCO3 crystals were obtained in an O/W emulsion with HABS to help deepen the understanding of the diversified growth of CaCO3 scaling in oilfields. As a result, rosette-like, bouquet-like, and dumbbell-shaped CaCO3 crystals with vaterite–aragonite, aragonite, and calcite–aragonite phases were formed with 200 mg/L HABS concentration at 45 °C for 60 min and spherical vaterite phase stabilized at a high HABS concentration (800 mg/L and 1000 mg/L). Rhombohedral calcite content experienced a fluctuation of about 40% as the HABS concentration varied. Needle-like and bundle-like aragonite precipitates were generated with increasing temperatures from 65 °C to 85 °C. Thus, HABS affects the nucleation and growth of the precipitated CaCO3 solid, leading to modifications in the structure and morphology of the crystals. The synergistic effect between HABS and temperature can regulate ion pairs with the calcium ions and block sites that are essential to the incorporation of new solutes into the crystal lattice, which leads to the heterogeneous nucleation of vaterite and aragonite on calcite, forming aragonite-based superstructures in kerosene emulsion. This work may enrich the understanding of CaCO3 mineralization in oilfields, and also provide a novel strategy for manufacturing organic–inorganic composites.